Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.


b) Evaluate the algebraic expression 2x2 + 5x +6 if x is equal to (-1).​


Sagot :

Step-by-step explanation:

if x is equal to - 1

Then

2x² + 5x + 6

= 2* ( -1)² + 5 * (- 1) + 6

= 2 - 5 + 6

= 8 - 5

= 3

Hope it will help :)❤

Answer:

if x=-1

then

2(-1)2+5(-1)+6

2(1)+5(-1)+6

2-5+6

X=+3